2017
DOI: 10.1002/jso.24905
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics, staging classification, and survival outcomes of primary malignant melanoma of the esophagus

Abstract: PMME is a considerably aggressive tumor with poor prognosis. The staging classification of mucosal melanoma of the upper aerodigestive tract may be a good option for PMME patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
3
23
1
1
Order By: Relevance
“…The PMME most commonly occurs in males, and the male-to-female ratio is 2:1, only 5 female patients were recorded in this study, which was similar to previous studies. [ 9 , 13 ] In the present study, there were 8 patients who failed to obtain accurate diagnosis by endoscopic biopsy before operation, including 3 cases of squamous cell carcinoma, 2 cases of adenocarcinoma, and 3 cases of malignant tumor. It was worth noting that among the 11 patients with PMME diagnosed by endoscopic biopsy before operation, 8 cases underwent immunohistochemical examination, which also suggested that immunohistochemical examination was of great significance in the diagnosis before operation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The PMME most commonly occurs in males, and the male-to-female ratio is 2:1, only 5 female patients were recorded in this study, which was similar to previous studies. [ 9 , 13 ] In the present study, there were 8 patients who failed to obtain accurate diagnosis by endoscopic biopsy before operation, including 3 cases of squamous cell carcinoma, 2 cases of adenocarcinoma, and 3 cases of malignant tumor. It was worth noting that among the 11 patients with PMME diagnosed by endoscopic biopsy before operation, 8 cases underwent immunohistochemical examination, which also suggested that immunohistochemical examination was of great significance in the diagnosis before operation.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that LNM was an independent prognostic factor in patients with esophageal squamous cell carcinoma. [ 13 , 17 – 19 ] Similarly, Wang et al analyzed the data of 13 PMME patients and also found that patients with LNM had a poor prognosis. [ 20 ] The present study found that patients with LNM had shorter OS time than that of without LNM.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the accuracy of biopsy is approximately 80%, and 20–50% of patients were misdiagnosed with poorly differentiated carcinoma because of absence of melanin granules [ 1 ]. Sun et al considered the reasons for misdiagnosis as follows: 1) some tumors are grossly amelanotic, and contain no melanin granules that are observable through microscopy, 2) melanocytes tend to concentrate in foci, and may thus be missed on biopsy, and 3) primary esophageal melanoma may be covered by normal squamous epithelium [ 16 ]. In our case, a detailed re-examination of biopsy tissue later revealed melanin with hematoxylin–eosin stain.…”
Section: Discussionmentioning
confidence: 99%
“…As a noncutaneous melanoma, PMME has been occasionally reported since 1906. [2] To date, about 337 cases of esophageal melanoma have been published, [4,8] whereas copresentation with gastric cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant melanoma occurs mostly in the skin and primary malignant melanoma of the esophagus (PMME) is very rare, accounting for approximately 0.1% to 0.2% of all esophageal tumors and 0.5% of all noncutaneous melanomas. [1,2] The average age of the patients with PMME is 60.5 years and the ratio of men to women is 2:1. [3] Along with the high aggressiveness of the disease, the median survival time of PMME is 13.4 months and 5-year overall survival rate is around 4%, [4,5] the rate may be improved to 37.5% after surgical resection according to a recent study.…”
Section: Introductionmentioning
confidence: 99%